2015
DOI: 10.1186/s12883-015-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of a self-management group program to improve social participation in patients with neuromuscular disease and chronic fatigue: protocol of the Energetic study

Abstract: BackgroundChronic fatigue is present in more than 60% of the patients with a neuromuscular disease and can be their most disabling symptom. In combination with other impairments, fatigue often results in low levels of physical activity and decreased social participation, leading to high societal costs. ‘Energetic’ is a self-management group program aimed at improving social participation, physical endurance and alleviating fatigue in these patients. The primary aim of this study is to evaluate the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…102,192,196 Emotional support tends to have a more beneficial impact in people living with pain than does Assessment of Function16 instrumental support (doing things for people) as the latter can lead to learned helplessness. 12 Studies have shown that both network size and quality of social support at diagnosis of rheumatoid arthritis patients, for example, predicts pain and functional status 3-5 years later.…”
Section: Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…102,192,196 Emotional support tends to have a more beneficial impact in people living with pain than does Assessment of Function16 instrumental support (doing things for people) as the latter can lead to learned helplessness. 12 Studies have shown that both network size and quality of social support at diagnosis of rheumatoid arthritis patients, for example, predicts pain and functional status 3-5 years later.…”
Section: Participationmentioning
confidence: 99%
“…12 Studies have shown that both network size and quality of social support at diagnosis of rheumatoid arthritis patients, for example, predicts pain and functional status 3-5 years later. 55 Given the emerging relevance of social participation, we recommend that assessment of social participation be considered in chronic pain clinical trials when the investigator believes that this construct may be perceived as a moderator or mediator in shaping the outcomes for a particular population under study 101,196 (See http://www.immpact.org/static/meetings/Immpact17/Williams.pptx). We identified 37 potential measures in the literature of which 17 were particularly relevant to the discussion.…”
Section: Participationmentioning
confidence: 99%
“…There is some qualitative evidence supporting that participation in home and social activities is important for promoting self-management in stroke patients (Berges et al, 2012;Horne et al, 2014). Evidence also indicates that higher self-efficacy is associated with increased social interaction behaviors (Craig et al, 2015;Veenhuizen et al, 2015). The level of selfefficacy involved in psychosocial functioning plays an important role in well-being in stroke survivors (Maujean and Davis, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…To date the programme's effectiveness has primarily been tested in North America [16,22,28] and Australia [20]; its merits are only beginning to be examined in European countries [23,29]. As such, despite its presence in the Swedish guidelines, the programme was essentially non-available in Sweden and there is a lack of research describing its use and feasibility in a Swedish context, with Swedish MS participants, and Swedish occupational therapists.…”
Section: Introductionmentioning
confidence: 99%